The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1017/s0033291723001678
|View full text |Cite
|
Sign up to set email alerts
|

Examining associations, moderators and mediators between childhood maltreatment, social functioning, and social cognition in psychotic disorders: a systematic review and meta-analysis

Abstract: Childhood maltreatment (CM) has been related to social functioning and social cognition impairment in people with psychotic disorders (PD); however, evidence across different CM subtypes and social domains remains less clear. We conducted a systematic review and meta-analysis to quantify associations between CM, overall and its different subtypes (physical/emotional/sexual abuse, physical/emotional neglect), and domains of social functioning and social cognition in adults with PD. We also examined moderators a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 169 publications
2
11
0
Order By: Relevance
“…Independent of CR, CM exposure was associated with higher subjective cognitive complaints and poorer neurocognitive function and psychosocial functioning in individuals with FEP, which is in line with previous research (Aas et al, 2011, 2012, 2014; Dauvermann & Donohoe, 2019; Hjelseng et al, 2022; Lantrip et al, 2023; Stain et al, 2014; Vargas et al, 2019). Also in line with previous work (only in females, though; Letkiewicz, Funkhouser, & Shankman, 2021), we found that in particular physical abuse was associated with poorer executive functioning, and that emotional neglect was associated with poorer interpersonal relationships (Fares-Otero, Alameda, et al, 2023; Haslam & Taylor, 2022) in FEP. However, our results linking emotional abuse with higher subjective cognitive complaints differ from prior study to date on the association between early traumatic events and subjective cognition, yet in people with current posttraumatic stress disorder symptoms (Lantrip et al, 2023).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Independent of CR, CM exposure was associated with higher subjective cognitive complaints and poorer neurocognitive function and psychosocial functioning in individuals with FEP, which is in line with previous research (Aas et al, 2011, 2012, 2014; Dauvermann & Donohoe, 2019; Hjelseng et al, 2022; Lantrip et al, 2023; Stain et al, 2014; Vargas et al, 2019). Also in line with previous work (only in females, though; Letkiewicz, Funkhouser, & Shankman, 2021), we found that in particular physical abuse was associated with poorer executive functioning, and that emotional neglect was associated with poorer interpersonal relationships (Fares-Otero, Alameda, et al, 2023; Haslam & Taylor, 2022) in FEP. However, our results linking emotional abuse with higher subjective cognitive complaints differ from prior study to date on the association between early traumatic events and subjective cognition, yet in people with current posttraumatic stress disorder symptoms (Lantrip et al, 2023).…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the association between emotional neglect and interpersonal relationships and leisure time was better at higher levels of CR. Although there is no definitive evidence on the association between CM and leisure time at this point (Fares-Otero, Alameda, et al, 2023), this pattern is in line with previous research (Buonocore et al, 2022) and may indicate that CR exerts control over social behavior and leisure time, and has the potential to improve autonomy and social life in those with FEP and a history of neglect. This lack of efficacy over social relations and behaviors is consistent with previous research on survivors (Conaway & Hansen, 1989; Haslam & Taylor, 2022).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations